A Pathfinder in High-Pressure Bioscience: In Memoriam of Gaston Hui Bon Hoa - Dmitri R. Davydov; Christiane Jung; Gregory A. Petsko; Stephen G. Sligar; Jack A. Kornblatt (Biology, 2021)
On 26 July 2020, our colleague and friend Dr [...]